2007
DOI: 10.1127/0078-0421/2006/0042-0075
|View full text |Cite
|
Sign up to set email alerts
|

Cyclostratigraphy concepts, definitions, and applications

Abstract: Abstract. Cyclostratigraphy is the subdiscipline of stratigraphy that deals with the identification, characterization, correlation, and interpretation of cyclic variations in the stratigraphic record and, in particular, with their application in geochronology by improving the accuracy and resolution of time-stratigraphic frameworks. As such it uses astronomical cycles of known periodicities to date and interpret the sedimentary record. The most important of these cycles are the Earth's orbital cycles of preces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(67 citation statements)
references
References 80 publications
0
63
0
4
Order By: Relevance
“…Both correlative conformities are downlapped by overlying regressive deposits, and may merge basinward with the main downlap surface (i.e., the maximum flooding surface) where the underlying highstand systems tract thins into a condensed section. Strasser et al (2006) illustrated how carbonate sedimentary cycles record repetitive changes (e.g., in stacking pattern, facies, biological and geochemical composition), often driven by periodic changes in accommodation. These are commonly attributed to changes in the Earth's orbital parameters that vary with pe-riods of 20 to 100 kyr.…”
Section: Carbonate Settingsmentioning
confidence: 99%
“…Both correlative conformities are downlapped by overlying regressive deposits, and may merge basinward with the main downlap surface (i.e., the maximum flooding surface) where the underlying highstand systems tract thins into a condensed section. Strasser et al (2006) illustrated how carbonate sedimentary cycles record repetitive changes (e.g., in stacking pattern, facies, biological and geochemical composition), often driven by periodic changes in accommodation. These are commonly attributed to changes in the Earth's orbital parameters that vary with pe-riods of 20 to 100 kyr.…”
Section: Carbonate Settingsmentioning
confidence: 99%
“…However, Milankovitch-band cycles may give discrete modes in the frequency distribution of sequence durations, albeit with slight change over geologic time, if they are not overprinted by other sequence-forming mechanisms that may operate within similar temporal scales. If it can be demonstrated that the hierarchy in the stacking of sequences was induced by orbital cycles, then the potential for the creation of a high-resolution time scale is presented (e. g., D'Argenio et al 1997;Strasser et al 2006).…”
Section: Hierarchy In Sequence Stratigraphymentioning
confidence: 99%
“…It uses astronomical cycles of known periodicities (Berger et al 1989) to interpret repetitive patterns in the sedimentary record (e. g., Strasser et al 2006) and to establish astro chrono logical time scales (e. g., Hinnov and Ogg 2007). Astronomical cycles cause insolation changes at the top of the atmosphere, which then translate into climate changes and eventually into eustatic sea-level changes, mainly through glacioeustasy and thermal expansion and retraction of the uppermost layer of ocean water.…”
Section: Links To Other Stratigraphic Disciplinesmentioning
confidence: 99%
“…These are typically of the last half billion years (the Phanerozoic Eon), where there are good fossil assemblages (i.e., biostratigraphy) that remain key to their definition, recognition, and correlation. Wherever feasible, additional tools, such as magnetostratigraphy, chemostratigraphy, sequence stratigraphy, cyclostratigraphy, and radiometric dating are employed (e.g., Strasser et al, 2006;Weissert et al, 2008;Langereis et al, 2010;Catuneanu et al, 2011;Gradstein et al, 2012). Most of the Precambrian units of the GTS, which largely lack useful fossil assemblages, remain defined by Global Standard Stratigraphic…”
Section: Introductionmentioning
confidence: 99%